A preliminary study through lymphocyte immunophenotyping of the effects of different forms of phosphorus deficiency on dairy cattle blood haematological parameters and immune status - Abramowicz Beata; Kurek Łukasz; Lisiecka Urszula; Żarczyńska Katarzyna (Journal of Veterinary Research, 2025)
The study determined the effects of different forms of phosphorus deficiency on white blood cell parameters in cows during the periparturient period and on the cows’ immune status.